CBMT-25. ANTI-TUMOR EFFECT OF VEGF INHIBITOR PLUS KETOGENIC DIET THERAPY FOR GLIOBLASTOMA - Maeyama, Masahiro (Neuro Oncol, 2018)
INTRODUCTION: Malignant glioma cells depend on glucose as the main energy source. Cancer cells may not be able to metabolize ketones as efficiently as normal brain cells, the ketogenic diet (KD) has been proposed as a complementary therapy for treatment of malignant gliomas. VEGF (vascular endothelial growth factor) inhibitor (bevacizumab) decreases blood supply to tumor and clinically used for glioblastoma treatment. Therefore, we examined anti-tumor effect of the combination of bevacizumab (Bev) and KD therapy using mouse model. METHODS: U87MG cells were implanted into the right brain of nude mice. One week after the implantation, mice were randomized into four treatment groups: control group, KD group, Bev group, and combination group. KetoCal 4:1 was administered to the mice for KD. Bev (10mg/kg) was injected from tail vein twice a week. Metabolic and histological analysis of the tumor, and survival analysis of the mice were performed. RESULTS: 3-hydroxy-butyrate, one of the ketone bodies, was increased in the tumor of KD group, and principal component analysis (PCA) analysis demonstrate distinct clustering or a clear separation of the four groups. Histologically, density of neovascularization was more increased in the combination group, compared with control, and phospho-ERK expression and Ki-67 index were decreased in the combination group. There was no different in body weight between KD group and other groups, and there was no different in survival time between KD group and control median overall survival 26 days vs 23 days, p=0.11. However, Bev group had significant longer survival than control group median OS 40 days, p=0.0016, and the combination group had most longer survival time among four groups median OS 50 days, p=0.0015. CONCLUSIONS: Drastic metabolic remodeling in the tumor occurred in the combination of Bev and KD. This combination may be potentially useful for glioblastoma therapy.